A Survey on Process Migration (International Journal of Advanced Research in Computer Science, 2017)
The days of supercomputers and mainframes dominating computing are over. With the cost benefits of the mass production of smaller machines, the majority of todayâ€™s computing power exists in the form of PCs or workstations, with more powerful machines performing more specialized tasks. Even with increased computer power and availability, some tasks require more resources. Load balancing and process migration allocates processes to interconnected workstations on a network to better take advantage of available resources. Process migration is the act of transferring a process between two machines during its execution. It enables dynamic load distribution, fault resilience, eased system administration, and data access locality. With the increasing deployment of distributed systems in general, and distributed operating systems in particular, process migration is receiving more attention in both research and product development. As high-performance facilities shift from supercomputers to networks of workstations, and with the ever-increasing role of the World Wide Web, we expect migration to play a more important role and eventually to be widely adopted. This paper reviews the field of process migration by summarizing the key concepts involved in it and by highlighting the benefits and challenges faced by the process migration. It also includes the experience of process migration in distributed operating system.Â Keywords: process migration, fault resilience, load distribution, distributed systems.